Behavioral analysis of Brazilian children participating in the “Baby’s Little Mouth Program” at Gurupi-Tocantins - Olegário da Costa, Isabel (My University, 2017)
The behavioral response of the child has been studied in some researches and is useful to predict how the child reacts to dental treatment, especially infants and young children, which is one of the greatest challenges of pediatric dentistry. Objective: To evaluate the behavioral pattern of children from 3 to 5 years of age in a preventive program in the municipality of Gurupi /Tocantins, Brazil. Materials and methods: This study was evaluated and approved by the Ethics and Research Committee. A total of 60 children, with different participation profiles of the program “Baby’s Little Mouth” were analyzed. Of these, 20 were frequent program participants, 20 were dropouts and 20 had never participated in the program before. The behavioral profile was analyzed by an external examiner, at the time of oral hygiene (prophylaxis), through the behavioral scale of Venham. Data were analyzed using Poisson regression analysis (α = 5%). Results: The children who presented the worst behavior were those who had never participated in the “Baby’s Little Mouth” program (OR=3.80; p=0.008), as well as children who did not allow brushing at home (OR=4.17; p=0.001) and those that only allowed brushing sometimes (OR=3.07; p=0.010). Conclusion: There is a positive influence of the program on psychological conditioning, on the anxiety of children and on the adoption of correct daily habits in their routines.
Análisis conductual de niños brasileños que participan del “Programa boquita del bebé” – Gurupi/Tocantins
Análise comportamental de crianças brasileiras participantes do “Programa Boquinha do Bebê” – Gurupi/Tocantins
PUBLISHED
Keywords: Pediatric dentistry; Behavioral management; Oral hygiene; Preventive programs